Pemberdayaan Perempuan Dalam Upaya Deteksi Dini Kanker Serviks Melalui Metode Reproductive Organ Self Examination (Rose) di Wilayah Kerja UPT Puskesmaskecamatan Sumbawa Unit 1 - Evi Gustia Kesuma; Haedar Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cervical cancer is the most common cancer in women, and mostly occurs in developing countries including Indonesia. In 2020, the World Health Organization found that cervical cancer was the seventh most common cause of death in the world, and caused 604,127 events annually. In the United States, cervical cancer cases are estimated at 13,800 cases of invasive cervical cancer and 4,290 deaths from cervical cancer occurred in 2020. For the ASEAN region, the incidence of cervical cancer in Singapore is 25.0 in Chinese, 17.8 in Malays, and Thai at 23.7 per 100,000 population. Every year there are about 90-100 new cases of cervical cancer, and every year about 40,000 people are affected by this disease. Cervical cancer ranks second as many as 36,633 or 9.20% of the total cancer cases in Indonesia in 2020. The purpose of this community service activity is to convey information about cervical cancer and improve early detection skills of cervical cancer with the ROSE method in women of childbearing age in the Working Area of the Puskesmas Sumbawa District Unit I. Reproductive Organ Self Examination (ROSE) is a simple method that can be done by mothers themselves to find out any problems in their reproductive organs. Health education needs to be done to improve mothers' knowledge and attitudes about cervical cancer. This community service activity aims to improve the behavior of mothers in the working area of UPT Puskesmas Sumbawa District Unit 1 in conducting early detection of cervical cancer through the IVA method and the ROSE technique and continued with questions and answers with activity participants. Women of childbearing age (WUS) in the Working Area of UPT Puskesmas Sumbawa District Unit I.